A critical evaluation of the Oscillayers methods and datasets. Issue 8 (13th April 2020) - Brown, Jason L.; Hill, Daniel J.; Haywood, Alan M.
Abstract: Here we evaluate Oscillayers, a new method that aims to estimate palaeoclimates for the past 5.4 Myr, and discuss the associated theoretical and methodological issues. We show that the theoretical foundation of Oscillayers is inherently limited, because the method cannot incorporate spatio‐temporal variation and different forcing mechanisms into climate reconstructions. In addition, several methodological weaknesses are clarified that entrench the palaeoclimatic reconstruction of Oscillayers to patterns of climate change observed between the Last Glacial Maximum and current climates. We test the utility of the Oscillayers method to produce palaeoclimatic reconstructions that are similar to general circulation model (GCM)‐based estimates. On average, only 55.6% of values in the mean annual temperature datasets across the Pliocene and Pleistocene were within ±3°C when compared with corresponding GCM‐based datasets. Furthermore, on average only 75.3% of values in the mean annual precipitation datasets across the Pliocene and Pleistocene were within ±200 mm of rainfall of the GCM‐based estimates. Our results demonstrate that the Oscillayers approach does not provide a robust approximation of palaeoclimatic conditions throughout the Plio‐Pleistocene. Thus, when these datasets are used for scientific analyses, the results should be interpreted with a full appreciation of their limitations, particularly for periods outside the last glacial cycle.